Exploring the Relationship Among Mental Health Concerns, Social Support, and Relationship Satisfaction in Female Same-Sex Couples. Issue Volume 12:Issues 1(2018) (2nd January 2018) - Terrell, Kassie R.; Dugger, Suzanne M.
ABSTRACT: The purpose of this quantitative study was to examine the relationship among internal factors (mental health concerns) that affect relationship satisfaction and contextual factors (social support) that affect relationship satisfaction in female same-sex couples (N = 99). Correlation and regression analyses indicated significant relationships among the variables. Specifically, mental health concerns were negatively correlated with relationship satisfaction whereas social support was positively correlated with relationship satisfaction. Mental health concerns and social support were found to be significant predictors of relationship satisfaction. Implications for practitioners are provided.